Two new species of the genus Dentigaster Zettel (Hymenoptera, Braconidae, Cheloninae) from Brazil - Dias, Manoel Martins; Penteado-Dias, Angélica Maria (Zootaxa, 2024)
Two new species of the genus Dentigaster Zettel, 1990 are described from brazilian fauna: Dentigaster medeirosi Dias & Penteado-Dias sp. nov., from Atlantic Forest and Dentigaster fernandesi sp. nov., from Cerrado.